T Follicular Helper Cell-Dependent Clearance of a Persistent Virus Infection Requires T Cell Expression of the Histone Demethylase UTX - Cook, Kevin D.; Shpargel, Karl B.; Starmer, Joshua; Whitfield-Larry, Fatima; Conley, Bridget; Allard, Denise E.; Rager, Julia E.; Fry, Rebecca C.; Davenport, Marsha L.; Magnuson, Terry; Whitmire, Jason K.; Su, Maureen A. (Immunity (Cambridge, Mass.), 2015)
Epigenetic changes, including histone methylation, control T cell differentiation and memory formation, though the enzymes that mediate these processes are not clear. We show that UTX, a histone H3 lysine 27 (H3K27) demethylase, supports T follicular helper (Tfh) cell responses that are essential for B cell antibody generation and the resolution of chronic viral infections. Mice with a T cell-specific UTX deletion had fewer Tfh cells, reduced germinal center responses, lacked virus-specific immunoglobulin G (IgG), and were unable to resolve chronic lymphocytic choriomeningitis virus infections. UTX-deficient T cells showed decreased expression of interleukin-6 receptor-α and other Tfh cell-related genes that were associated with increased H3K27 methylation. Additionally, Turner Syndrome subjects, who are predisposed to chronic ear infections, had reduced UTX expression in immune cells and decreased circulating CD4+ CXCR5+ T cell frequency. Thus, we identify a critical link between UTX in T cells and immunity to infection. [Display omitted] •T cell expression of UTX is required to clear a chronic virus infection•UTX supports Tfh cell differentiation and subsequent B cell & antibody responses•UTX-mediated H3K27me3 demethylation enforces Tfh gene-expression profile•UTX expression and CD4+ CXCR5+ T cell frequency are reduced in Turner Syndrome T cell differentiation depends on changes in histone methylation, but the enzymes regulating these processes are unknown. Whitmire and colleagues demonstrate that the H3K27me3 demethylase UTX sustains T follicular helper cells, antiviral antibody production, and clearance of chronic virus infection through regulation of IL-6Rα and other Tfh-related genes.